Influência de pressões de trabalho, espaçamentos e altura de instalação na distribuição de água de aspersor autocompensante - Oliveira, Vinicius Mendes Rodrigues de [UNESP] (2015)
Actually, there is great concern about the waste of water. When using equipment and systems that have more uniform water distribution, it will have better utilization of the applied water. The objective of this study was to evaluate the performance of the model FR Super 10 sprinkler with pressure compensator under different pressures, spacing and installation heights. The tests were performed in the laboratory, controlling the pressure with two gauges calibrated with mercury column and the distribution uniformity measured using the Christiansen uniformity coefficient (CUC) and the distribution uniformity coefficient (CUD). Four spray nozzles were utilized in the Super 10 sprinkler, two heights (0.6 and 1.2 m), six pressures (25, 30, 35, 40, 45 and 50 m H2O) and six spacing (9x9, 9x10, 10x10, 9x12, 10x12 and 12x12 m). The blue, yellow and red nozzles presented self-compensating features and green nozzle was not fully self- compensating, the coefficients manufacturing variations (CVF) were lower in the nozzles with smaller aperture (blue and yellow) compared to the higher nozzle opening. Increasing the sprinkler height provides better water uniformity distribution and of the radial distribution profile, lowering the application rate near the sprinkler. As this sprinkler has compensator pressure change the pressure did not influence the sprinkler range